MOVING OBJECT DETECTION BY USING OPTICAL FLOW - Sanap Vaishali Arjun; Prof.M.B.Kadu; Prof.R.P.Labade (International Journal of Innovations in Engineering Research and Technology, 2021)
Applications like surveillance, robotics etc the computer and machine vision are the important and useful area of research. As one of the vital part of computer vision, object tracking plays a critical role in numerous lines of research such as human and non-human activity recognition, 3D representation and 3D reconstruction, augmented reality, video surveillance, and robotics etc. In the past decades for the object detection and tracking many researchers have developed their own algorithms, but developing a robust tracker is still a challenging task due to many intrinsic and extrinsic limitations like appearance change of a target object (anthropometric variations), change in view point, cluttered background, varying illumination, camera motion, and occlusions etc. This proposed algorithm detects and tracks the objects present the video. As video is nothing but the sequence of images or frames, the tracker should track the object from these consecutive frames successfully. Optical flow algorithm is used for object tracking.